irpll The Impacts of War and Violence on Pashtunwali: A Case Study of FATA: Allaudin, Muhammad Yousaf Storai,Dr.Mirwise Kasi - jan, abdullah (JPL, 2023)
Pashtun society was or is a typically passive, peace loving or literature loving society with its own complete code of life that is Pashtunwali. Pashtunwali governs all the aspects of tribal life in Pashtun society but with foreign intervention in Afghanistan in 1979 rippled the silent waves in Pashtun society. In short the consequences of Soviet invasion in 1979 and shoddier law and order situation; since that time, in Pashtun areas harmed the well establish norms and values of the Pashtun society. Cross border movements, sanctuaries and base camps on the either side of the Durand Line, movement of arms and ammunition, financial and logistic support created and formulated the sense of militancy and violence in Pashtun society, which accustomed the values and commencements of Pashtunwali. This study is designed to introduce Pashtunwali in original form through the available literature and discussed the main commencements of Pashtunwali. Violence and war in Pashtun areas are briefly discussed to provide basis for the study. The impacts of war are the main focus of this study that is being comparatively discussed with effects upon the customary law of Pashtun society.